The Influence of Motivation, Work Discipline and Workload on Employee Performance at MAN 2 Mojokerto - Ifanul Khabibah; Sri Rahayu; Sundjoto Sundjoto (CV. Rayyan Dwi Bharata, 2024)
The aim of this research is to determine the influences that can influence employee performance at MAN 2 Mojokerto which include work motivation, work discipline and workload, either partially, simultaneously or dominantly. The research method used in this research is a quantitative method involving all ASN and non-ASN employees in the MAN 2 Mojokerto area, totaling 123 people. With the probability sampling method and using saturated sampling techniques. The data collection technique used was a questionnaire. The data analysis method used is hypothesis testing, multiple linear regression analysis, coefficient of determination. Based on the research results, it shows that the work motivation variable has a significant effect on employee performance at MAN 2 Mojokerto. The Work Discipline variable has a significant effect on employee performance at MAN 2 Mojokerto. The Workload variable has a significant effect on employee performance at MAN 2 Mojokerto. The variables of motivation, discipline and workload simultaneously have a significant effect on employee performance at MAN 2 Mojokerto. The work discipline variable is an independent variable that has a dominant influence on employee performance at MAN 2 Mojokerto.